2001
DOI: 10.1074/jbc.m105049200
|View full text |Cite
|
Sign up to set email alerts
|

Rac Affects Invasion of Human Renal Cell Carcinomas by Up-regulating Tissue Inhibitor of Metalloproteinases (TIMP)-1 and TIMP-2 Expression

Abstract: Rho-like GTPases, including Cdc42, Rac1, and RhoA, regulate distinct actin cytoskeleton changes required for adhesion, migration, and invasion of cells. Tiam1 specifically activates Rac, and earlier studies have demonstrated that Tiam1-Rac signaling affects migration and invasion in a cell type-and cell substrate-specific manner. In the present study, we examined the role of Tiam1-Rac signaling in migration and invasion of human renal cell carcinomas. Stable overexpression of Tiam1 or constitutively active V12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 49 publications
3
78
1
1
Order By: Relevance
“…Interestingly, the effects of Rac1 on migration and invasion in vitro may be either stimulating or inhibitory, depending on the cell-substrate used, the fact as to whether or not the formation of E-cadherin-mediated cell-cell adhesions is prevented, and the cell type studied (Sander et al 1998, Braga et al 1999, Engers et al 2001, Price & Collard 2001. Given these heterogeneous effects of Rac1 on migration and invasion of epithelial cells in vitro, the effect of increased Rac expression in a given tumor in vivo on DFS might be positive or negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the effects of Rac1 on migration and invasion in vitro may be either stimulating or inhibitory, depending on the cell-substrate used, the fact as to whether or not the formation of E-cadherin-mediated cell-cell adhesions is prevented, and the cell type studied (Sander et al 1998, Braga et al 1999, Engers et al 2001, Price & Collard 2001. Given these heterogeneous effects of Rac1 on migration and invasion of epithelial cells in vitro, the effect of increased Rac expression in a given tumor in vivo on DFS might be positive or negative.…”
Section: Discussionmentioning
confidence: 99%
“…So far, three highly homologous Rac proteins have been described in mammals: the ubiquitous Rac1, the hematopoiesis-specific Rac2, and the least-characterized Rac3 (for review see: Wennerberg & Der 2004). Rac1 is a major regulator of the actin cytoskeleton (Ridley et al 1992), which affects cell cycle progression (Olson et al 1995), cell adhesion (Hordijk et al 1997, Kuroda et al 1998, migration (Keely et al 1997, Sander et al 1998, Engers et al 2001, invasion (Hordijk et al 1997, Keely et al 1997, Engers et al 2001, 2006b, and metastasis (Shan et al 2005) of tumor cells. Moreover, Rac1 has been implicated in oncogenic transformation of cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in oncogenic transformation, Tiam1 has also been implicated in the regulation of migration, invasion, and metastasis of tumour cells (Habets et al, 1994;Hordijk et al, 1997;Adam et al, 2001;Engers et al, 2001). Interestingly, the effects of Tiam1 on migration and invasion in vitro may be either stimulating or inhibitory, depending on the cell-substrate used, the fact as to whether or not the formation of E-cadherin-mediated cell -cell adhesions is prevented, and the cell type studied (Sander et al, 1998;Engers et al, 2001;Price and Collard, 2001;Minard et al, 2004). Given these heterogeneous effects of Tiam1 on migration and invasion of epithelial cells in vitro, the effect of increased Tiam1 expression in a given tumour in vivo on DFS might be positive or negative.…”
Section: Discussionmentioning
confidence: 99%
“…As a negative control, representative sections were subjected to the same immunostaining procedure except for the fact that the primary antibody was omitted. As a positive control, paraffinembedded tumour spheroids of Tiam1-transfected renal carcinoma cells (Engers et al, 2001) were used. The specificity of the Tiam1 antibody used in this study has previously been demonstrated (Habets et al, 1994;Malliri et al, 2002).…”
Section: Pathological and Immunohistochemical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation